All Days 2008
DOI: 10.2118/114375-ms
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Reservoir Performance of the Messoyakha Gas Hydrate Reservoir

Abstract: The Messoyakha Gas Field is located in Siberian permafrost. The field has been described as a free gas zone, overlaid by hydrate layer and underlain by an aquifer of unknown strength. The field was put on production in 1970 and has produced intermittently since then. Some characteristic observations were increase in average reservoir pressure during shut-in, perforation blocking due hydrate formation and no change in gas-water contact. It is believed the increase in reservoir pressure was caused by the hydrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 8 publications
1
18
0
2
Order By: Relevance
“…It was estimated that about 36% (5.17 × 10 9 m 3 ) of the gas produced was from the hydrate zone [29,38]. While a review of available geological, geochemical and production data by Collett and Ginsburg [29,39] indicated that the overlying gas hydrates may not have been contributing significantly to gas production, in a more recent numerical simulation study of the Messoyakha field, results similar to the actual reported flow rates and pressure behaviour were observed [40]. The results of the numerical simulation study indicated that as much as 15-20% of the gas produced from the Messoyakha field came from dissociation.…”
Section: Arctic Accumulationsmentioning
confidence: 78%
“…It was estimated that about 36% (5.17 × 10 9 m 3 ) of the gas produced was from the hydrate zone [29,38]. While a review of available geological, geochemical and production data by Collett and Ginsburg [29,39] indicated that the overlying gas hydrates may not have been contributing significantly to gas production, in a more recent numerical simulation study of the Messoyakha field, results similar to the actual reported flow rates and pressure behaviour were observed [40]. The results of the numerical simulation study indicated that as much as 15-20% of the gas produced from the Messoyakha field came from dissociation.…”
Section: Arctic Accumulationsmentioning
confidence: 78%
“…The value of dimension width, 400 m, was set after referenced Grover' physical model whose value was 350 m in diameter [7]. The horizonal length was set as 1495.2 m to ensure that the reservoirs contain large amount of hydrates, and if correct strategy were taken, large amount of natural gas would be produced.…”
Section: Reservoirs Discretizationmentioning
confidence: 99%
“…Many countries paid great attention to hydrates with the traditional fossil energy exhaustion and its wide range of applications developed in many field [3]. America had made all-round studies on hydrate dissociation in industry level [4][5][6][7]. Japan had made long-term strategies on the gas hydrates exploitation from Nankai Trough, and they hoped the hydrate reservoirs in Nankai Trough could be dissociated in the near future [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Through the methods of depressurization, heat shock, chemical injection, and replacement, methane gas is released by hydrates decomposition or replacement, and then is produced. Existing examples of exploiting natural gas hydrate reservoir are mainly included as follows: In the Messoyakha gas field of Siberia area, the gas is produced from hydrate decomposition by means of depressurization and chemical injection . In the Mallik area of Canada, two hydrate samples were tested by means of depressurization and heat injection .…”
Section: Introductionmentioning
confidence: 99%